Analysis of Junior High School Students' Learning Difficulties in Solving Statistics Problems as a Basis for Developing RME-Based Learning Materials - Muhammad Fahri Firdaus; Titi Rohaeti; Sumliyah Sumliyah (MASI Mandiri Edukasi, 2026)
This study aims to analyze the learning difficulties junior high school students face in solving statistics problems based on Realistic Mathematics Education (RME) principles, to support the development of learning materials. This study used a qualitative, descriptive approach and was conducted at SMPN 1 Pasawahan, Kuningan Regency, West Java, during the even semester of the 2025/2026 academic year. Thirty-five students completed a written test, after which three students were purposively selected to represent high (CA), medium (NN), and low (MR) ability levels. Research instruments included a written essay test comprising six RME-based contextual problems and a semi-structured interview guide. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing, utilizing triangulation between written responses and interview results. The findings indicate that students' learning difficulties varied by ability level. High-ability students were able to solve almost all problems but encountered obstacles in understanding the meaning of consistency in statistics and applying the interquartile range ( ) formula. Medium-ability students experienced difficulties regarding quartile concepts and time management, as they were unaccustomed to lengthy contextual problems. Low-ability students faced fundamental hurdles in interpreting visual representations (pie charts), grasping basic statistical concepts, and drawing conclusions from data; they also could not complete most problems due to time constraints. These findings underscore the need for RME-based learning materials that integrate real-life contexts, visual aids (scaffolding), and explicit practice in drawing conclusions from data.